The reactions of 2-ethoxymethylidene-3-oxo esters and their analogues with 5-aminotetrazole as a way to novel azaheterocycles - Goryaeva, Marina V.; Burgart, Yanina V.; Ezhikova, Marina A.; Kodess, Mikhail I.; Saloutin, Viktor I. (Beilstein Journal of Organic Chemistry, 2015)
The interaction of 2-ethoxymethylidene-3-oxo esters and their analogues with 5-aminotetrazole is an efficient synthetic approach to novel azaheterocycles. 2-Ethoxymethylidene-3-oxo esters bearing alkyl substituents react with 5-aminotetrazole to form ethyl 2-azido-4-alkylpyrimidine-5-carboxylates which are capable of subsequent nucleophilic substitution. The use of diethyl 2-ethoxymethylidenemalonate in this reaction resulted in ethyl 7-hydroxytetrazolo[1,5-a]pyrimidine-6-carboxylate, while ethyl 2-ethoxymethylidenecyanoacetate yielded 5-[2,6-diamino-3,5-bis(ethoxycarbonyl)pyridinium-1-yl]tetrazol-1-ide through an alternative pathway. Ethyl 2-benzoyl-3-ethoxyprop-2-enoate reacted with 5-aminotetrazole by two reaction routes to form ethyl 2-benzoyl-3-(1H-tetrazol-5-ylamino)prop-2-enoate and ethyl 7-(1-ethoxy-1,3-dioxo-3-phenylpropan-2-yl)-5-phenyl-4,7-dihydrotetrazolo[1,5-a]pyrimidine-6-carboxylate.
Keywords: 5-aminotetrazole; cyclisation; diethyl 2-ethoxymethylidenemalonate; 2-ethoxymethylidene-3-oxo esters; ethyl 2-ethoxymethylidenecyanoacetate